Treatment of biologically treated distillery spent wash employing electrocoagulation and reverse-osmosis treatment train. Issue 27 (6th December 2022) - Sharma, Pinki; Joshi, Himanshu; Srivastava, Vimal Chandra; Singh, Seema; Lo, Shang-Lien
ABSTRACT: In the present study, electro-coagulation (EC) with stainless steel (SS) electrodes has been used as a pretreatment process before the reverse osmosis (RO) for the biologically treated distillery spent wash. The optimized operating parameters (pH, time, current, and electrode distance) for the EC process were obtained from the previous study. EC treated wastewater was further used as a feed for the RO system. RO membrane system operating parameters (pH, temperature, and trans-membrane pressure) were optimized by employing response surface methodology. Optimized conditions for the RO process were found to be: pH (pHo ): 6.12; temperature (T): 20°C and trans-membrane pressure (TMP): 45.7 bar. The combined (EC-RO) process showed 98%, 99.2%, and 98.5% of COD, color, and TDS removal, respectively, with permeate flux of 40.5 L/m 2 /h (EC-RO). Experimental results indicated that EC followed by RO could be used as an additional step for biologically treated spent wash treatment to improve the treated effluent quality and membrane life. Results also revealed that the techno-economic performance of combined (EC-RO) treatment in terms of total annual water production is more efficient and economical than RO alone. GRAPHICAL ABSTRACT: UF0001